2022
DOI: 10.3389/fendo.2022.907914
|View full text |Cite
|
Sign up to set email alerts
|

Interest of Bone Histomorphometry in Bone Pathophysiology Investigation: Foundation, Present, and Future

Abstract: Despite the development of non-invasive methods, bone histomorphometry remains the only method to analyze bone at the tissue and cell levels. Quantitative analysis of transiliac bone sections requires strict methodologic conditions but since its foundation more 60 years ago, this methodology has progressed. Our purpose was to review the evolution of bone histomorphometry over the years and its contribution to the knowledge of bone tissue metabolism under normal and pathological conditions and the understanding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 214 publications
0
10
0
Order By: Relevance
“…In this study, we only included papers reporting osteoclast indices for OI patients prior to treatment with bisphosphonate or after the drug holiday to minimize the treatment effect on osteoclast physiology. Osteoclast function in clinical studies can be assessed by bone histomorphometry, which requires invasive transiliac biopsy 17 or by examining blood or urine levels of collagen degradation markers indicative of increased bone turnover 80 . Previously, prominent increases in bone resorption markers were reported in OI children 29,35,37 , while osteoclast indices in bone histomorphometry were variably affected 11,25 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we only included papers reporting osteoclast indices for OI patients prior to treatment with bisphosphonate or after the drug holiday to minimize the treatment effect on osteoclast physiology. Osteoclast function in clinical studies can be assessed by bone histomorphometry, which requires invasive transiliac biopsy 17 or by examining blood or urine levels of collagen degradation markers indicative of increased bone turnover 80 . Previously, prominent increases in bone resorption markers were reported in OI children 29,35,37 , while osteoclast indices in bone histomorphometry were variably affected 11,25 .…”
Section: Discussionmentioning
confidence: 99%
“…The following data items relevant to study characteristics were extracted (Supplemental materials): i) for all studies: authors; publication year and country; ii) for studies involving human subjects: publication type (case report or clinical study), age; sex; OI type (when given); OI severity (when given); sample size; control groups (when given); type of diagnosis (clinical or genetic or family history); treatments (when given) and study design; iii) for animal studies using mouse models of OI: strain; genotype; age; sex; OI severity (when given); sample size; control groups and treatment (when given). For the osteoclast related outcomes, we extracted the data for OI and control group for urine or serum levels of collagen degradation markers, C-terminal telopeptide of type 1 collagen (CTX), N-terminal telopeptide of type 1 collagen (NTX) or urinary deoxypyridinoline (DPD) 16 , and osteoclast parameters from bone histomorphometric analysis (osteoclast number, osteoclast surface, resorptive surface and eroded surface 17 ). Data items included bone type and bone region being measured; type of bone turnover marker; measurement technique; mean or median (as applicable) and standard errors, standard deviations, and/or interquartile ranges of reported outcomes.…”
Section: Data Extraction Data Items and Conversionmentioning
confidence: 99%
“…Bone histomorphometry remains the only method to analyze bone at the tissue and cell levels despite the development of noninvasive approaches [ 41 , 42 ]. Under histologic observations, it has been confirmed that ADB demonstrates biological compatibility and does not cause any significant inflammatory reaction.…”
Section: Discussionmentioning
confidence: 99%
“…A detailed review of the use of bone morphometry for clinical medicine and research can be found here. 23 …”
Section: History and Evolution Of Bone Morphometrymentioning
confidence: 99%